The storm is upon us : how QAnon became a movement, cult, and conspiracy theory of everything - Rothschild, Mike (Melville House, 2021)
A journalist who specializes in conspiracy theories draws on interviews with QAnon converts and victims, as well as psychologists, sociologists, and academics to explain the origin and growth of the movement, its embrace by right-wing media and politicians, and why it is important to understand it rather than mock it.